PENGARUH STRUKTUR SISTEM PENGENDALIAN MANAJEMEN, PROSES SISTEM PENGENDALIAN MANAJEMEN DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL (STUDI PADA RSUD SULAWESI UTARA) - Tendean, Anggreini Brenda; Saerang, David P. E.; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Increasing managerial performance is important for an organization so that the goals of an organization can be achieved. Performance is the work of someone in the organization in carrying out the duties and responsibilities that apply in an organization. Several factors that influence managerial performance include the management control system structure, the management control system process and the reward system. This study aims to determine the effect of the structure of the management control system, the process of management control systems and the reward system on managerial performance in the general hospitals of North Sulawesi. The sample used was 40 respondents. The results of the first hypothesis testing obtained t-count value of 14.066> 2.028 and a significance value of 0.000 <0.05. Thus the hypothesis of the structure of the management control system has a significant positive effect on managerial performance received in accordance with the results of the partial hypothesis test (t test). This shows that North Sulawesi Hospital has implemented a management control system structure that can improve hospital managerial performance. The second hypothesis is obtained by the t-count value of 2.185> 2.028 and the significance value of 0.035 <0.05. Thus the hypothesis of the management control system process has a significant positive effect on managerial performance received in accordance with the results of the partial hypothesis test (t test). This shows that the better the implementation of the management control system process, the managerial performance will increase. The third hypothesis is obtained that the t-count value is 2.021 <2.028 and the significance value is 0.051> 0.05. Thus the reward system hypothesis influences managerial performance is rejected in accordance with the results of the partial hypothesis test (t test). This shows that the reward system applied by the hospital does not affect managerial performance. And the fourth hypothesis is obtained F-count value of 84.200> 2.86 and a significance value of 0.000 <0.05. Thus the hypothesis of the structure of the management control system, the management control system process and the reward system are accepted in accordance with the results of simultaneous hypothesis testing (F test).Keywords: Structure of Management Control Systems, Process of Management Control Systems, Reward Systems, Managerial Performance.